PERAN PSAK 109 DALAM PENINGKATAN AKUNTABILITAS DAN TRANSPARANSI PELAPORAN ZAKAT DI INDONESIA - Muji Astuti (Universitas Bunda Mulia, 2018)
The growth of zakah, donation/charity increases every year, though still far from zakah potential estimated by various research institutions. The collection and distribution of zakat, donation/charity is accountably reported to the public in the form of financial statements based on the principles of accountability and transparency. Accountability is associated with the fulfillment of the muzaki expectations to gain and enlarge benefits perceived by mustahik. Transparency is manifested in the publication of the financial statements were prepared based on the financial standards and audited by an independent institution. Transparency and accountability in the dimension of Islam not only worldly but also hereafter, be accountable to Allah SWT. The established of PSAK (Statement of Financial Accounting Standards) 109 at the end of 2011 as the accounting standards of the organization of zakah and donation/charity in Indonesia became a binding foundation for preparing financial statements. This paper describes the application of accounting standards on financial statements of zakah institutions to measure the fulfillment of accountability and transparency, by comparing the reports before and after PSAK 109. The results of this study hopefully will give the contribution to the zakat management organizations in completing the public's expectations in the optimization benefits. Keywords: management of zakat in Indonesia, accountability, transparency, accounting standards, the financial statement.